Penyuluhan tentang Pengelolaan Shivering Pasca Sektio Caesarea untuk Meningkatkan Kualitas Perawatan Pasien - Nabhani Nabhani; Mustika Sari (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Shivering after cesarean section is one of the common side effects of spinal anesthesia that is often overlooked but can cause significant discomfort, even increasing the risk of postoperative complications such as increased oxygen consumption and impaired recovery. This community service program aims to improve understanding in both patients and health workers regarding the importance of effective shivering management through health education and practical training. The methods used include socialization, interactive counseling, action simulation, and evaluation of the level of understanding before and after educational activities. The results showed an increase in patient knowledge from 50% to 85% after education, and a decrease in the incidence of shivering from 70% to 30% after implementation of the intervention. These findings indicate that educational interventions and promotive-preventive approaches play an important role in improving the quality of postoperative care, especially in patients undergoing cesarean section. Therefore, the active involvement of health workers in providing health information and non-pharmacological pain management is essential to prevent and overcome shivering optimally.